Vacancy-solute interactions during multiple-step ageing of an Al-Cu-Mg-Ag alloy - Ferragut, Rafael Omar (2009)
Small additions of Ag and Mg stimulate nucleation of the Ω phase in artificially aged Al-Cu alloys, after which these elements segregate to the Ω/matrix interfaces. In this work, positron spectroscopy results show that vacancies accompany the Ag (and Mg) atoms at the interface during precipitate formation, after which they are released back into the matrix and facilitate secondary ageing at ambient temperature.